2012
DOI: 10.1155/2012/829584
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Exhausted B Cells in Asymptomatic HIV-1-Infected Patients Naïve for HAART is Related to Reduced Immune Surveillance

Abstract: Alterations of B cell subpopulations have been described up to date as characterizing advanced stage of HIV-1 infection. However, whether such defects are relevant in subjects with a preserved number of CD4+ T cells (>350 cells/μL) is unclear. In a cross-sectional study, we investigated if signs of B cells exhaustion and impaired viral immune surveillance are present in a cohort of 43 asymptomatic HIV-1-infected patients with preserved CD4+ T cell counts (>350 cells/μL) and highly active antiretroviral therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 34 publications
1
23
0
1
Order By: Relevance
“…Our group and others have reported an association between TTV viraemia and the extent of immune deficiency, whether the latter is congenital (Maggi et al, 2011) or acquired (iatrogenic) Maggi et al, 2008), due to cancer (Zhong et al, 2001(Zhong et al, , 2002 or to chronic infections (Fogli et al, 2012). In 2008, we described, using a quantitative real-time PCR assay targeting conserved TTV genome regions in myeloma and lymphoma patients receiving highdose chemotherapy, a clear correlation between peaks of total TTV viraemia and expansion of senescent CD8 +…”
Section: Introductionmentioning
confidence: 59%
“…Our group and others have reported an association between TTV viraemia and the extent of immune deficiency, whether the latter is congenital (Maggi et al, 2011) or acquired (iatrogenic) Maggi et al, 2008), due to cancer (Zhong et al, 2001(Zhong et al, , 2002 or to chronic infections (Fogli et al, 2012). In 2008, we described, using a quantitative real-time PCR assay targeting conserved TTV genome regions in myeloma and lymphoma patients receiving highdose chemotherapy, a clear correlation between peaks of total TTV viraemia and expansion of senescent CD8 +…”
Section: Introductionmentioning
confidence: 59%
“…An exhausted B-cell phenotype has been previously associated with a CD27 − CD21 lo "tissue-like memory" B-cell subset in HIV-infected subjects [15], a subset that has been variably associated with viral load and treatment status [32,33]. This B-cell subset has been found to exhibit lesser proliferation with BCR engagement plus CD40 ligation or BCR engagement plus TLR9 ligation, but the hypoproliferative "exhausted" phenotype could be partially overcome by combining all three stimuli [15,34].…”
Section: Discussionmentioning
confidence: 99%
“…Prospective association of chronic viral antigenic stimulation (or chronic CpG or LPS exposure) leading to expansion of CD27 − CD21 − B-cells has not been established in humans. However, successful viral control under ART therapy of HIV disease has been associated with reduction of CD27 − CD21 lo B-cells in one study [32]. In HCV, CD27 − CD21 lo B-cells have been associated with virus-induced clonally expanded Bcells [17,38].…”
Section: Discussionmentioning
confidence: 99%
“…CD10 staining in HIV-infected individuals can be variable. Fogli et al (18) reported previously that levels of CD21 Ϫ CD27 Ϫ tissue-like memory cells are elevated in HIVinfected patients and that these cells are essentially negative for CD10, representing an exhausted phenotype. Malaspina et al (34) reported previously that the elevated CD21 Ϫ CD27 Ϫ cell population in HIV-positive individuals could be either CD10 ϩ , representing immature cells, or CD10…”
Section: Cd20mentioning
confidence: 98%